Genetic analysis of four cases of Poirier Bienvenu neurodevelopmental syndrome associated with CSNK2B variant - Liu Yang; Daoqi Mei; Yanping Liu; Li Gao (BMC Medical Genomics)
Abstract Background CSNK2B deficiency underlies the pathogenesis of Poirier-Bienvenu neurodevelopmental syndrome (POBINDS). In this study, we present four cases of pediatric seizures caused by de novo variants in CSNK2B, with the aim to reinforce the clinical and variant data pertaining to early genetic factors associated with epilepsy. Methods Trio whole exome sequencing were used to detect variants in the proband and her family members, and bioinformatics annotation was performed for the variant. Sanger sequencing and CSNK2B cDNA sequencing were employed to ascertain the carrier status of additional family members and evaluate the potential impact of variants on splicing. Results All four cases presented with epilepsy as the initial manifestation, accompanied by global developmental delay, particularly in language and motor developmental delay. Cases 1, 3 and 4 exhibited full-scale tonic-clonic seizures, while case 2 displayed myoclonic and typical absence seizures. Furthermore, case 2 demonstrated delayed growth and development compared to age-matched peers. No abnormality was detected in the head magnetic resonance imaging (MRI). Genetic analysis revealed novel heterozygous variants in the CSNK2B gene in all four cases, including c.175 + 1G > A, c.73-2A > G, c.291 + 1G > A and c.481delA. In case 2, reverse transcription analysis of CSNK2B mRNA revealed the retention of the 3’ end sequence of Intron 2 and deletion of the 5’ end sequence of Exon 3. In treatment, four case received a combination of one to three types of antiseizure medication and rehabilitation training individually. Case 1 continued to experience seizures to varying degrees, while cases 2–4 demonstrated effective seizure control. Overall motor and intellectual development improved in all four cases, however, there was slow recovery in language function. Conclusion This study elucidates the molecular etiology of epilepsy in four cases with POBINDS and expands the mutational spectrum of pathogenic variants in the CSNK2B, highlighting their impact on splicing. The highly genetic heterogeneous phenotype of POBINDS relies on the detection of pathogenic variants in CSNK2B. Conventional antiseizure medication effectively control seizures, while rehabilitation treatment can significantly improve intelligence and motor function to varying degrees; however, language recovery tends to be relatively slow.